Formation quality optimization of laser hot wire cladding for repairing martensite precipitation hardening stainless steel - Wen, Peng; Feng, Zhenhua; Zheng, Shiqing (Optics and laser technology, 2015)
Laser cladding is an advantaged repairing technology due to its low heat input and high flexibility. With preheating wire by resistance heat, laser hot wire cladding shows better process stability and higher deposition efficiency compared to laser cold wire/powder cladding. Multi-pass layer were cladded on the surface of martensite precipitation hardening stainless steel FV520B by fiber laser with ER410NiMo wire. Wire feed rate and preheat current were optimized to obtain stable wire transfer, which guaranteed good formation quality of single pass cladding. Response surface methodology (RSM) was used to optimize processing parameters and predict formation quality of multi-pass cladding. Laser power P, scanning speed Vs, wire feed rate Vf and overlap ratio η were selected as the input variables, while flatness ratio, dilution and incomplete fusion value as the responses. Optimal clad layer with flat surface, low dilution and no incomplete fusion was obtained by appropriately reducing Vf, and increasing P, Vs and η. No defect like pore or crack was found. The tensile strength and impact toughness of the clad layer is respectively 96% and 86% of those of the substrate. The clad layer showed nonuniform microstructure and was divided into quenched areas with coarse lath martensite and tempered areas with tempered martensite due to different thermal cycles in adjacent areas. The tempered areas showed similar hardness to the substrate. •The influence of multiple parameters on formation quality is concluded.•The optimal parameters are predicted by response surface method.•Good formation quality with large dimension of clad layers is stably obtained.•The clad shows uneven microstructure, divided into quenched and tempered martensite.•The tensile strength of clad is 96% of the substrate, while impact toughness 86%.